Gambaran Pengetahuan Siswa SMA Negeri 2 Langowan Tentang Pernikahan Dini - Christina Christina; Maxi Marthen Luther Moleong; Nancy Sylvia Bawiling (Yayasan Syalom Cipta Sumikolah, 2025)
Early marriage is defined as marriage occurring before the age of 19, which carries risks of various negative impacts from reproductive health, psychological, social, and economic perspectives. This study aims to determine the knowledge of students at SMA Negeri 2 Langowan regarding early marriage. The research method used was quantitative descriptive with a cross-sectional design. The study population consisted of 210 students, with a sample of 68 students selected using stratified random sampling. The results showed that the majority of students at SMA Negeri 2 Langowan had good knowledge about early marriage, with 54 respondents (79.4%). Regarding knowledge of the factors causing early marriage, the majority had adequate knowledge, with 47 respondents (69.1%). Regarding students' knowledge of the impacts of early marriage, the majority had adequate knowledge, with 42 respondents (61.8%). Additionally, regarding the use of contraception, the majority of students had adequate knowledge, with 34 respondents (50.0%). The conclusion is that the majority of students at SMA Negeri 2 Langowan already have adequate knowledge about early marriage, its causes, its impacts, and the use of contraception. Recommendation: It is hoped that this study can provide information so that SMA Negeri 2 Langowan can collaborate with the Community Health Center to conduct counseling for students about early marriage and the dangers of premarital sex.